Pola Struktur dan Konfigurasi Geologi Bawah Permukaan Cekungan Jawa Barat Utara berdasarkan Analisis Gayaberat - Setiadi, Imam; Pratama, Achmad Wahyu (Pusat Survei Geologi, 2018)
North West Java Basin consists of several subbasins formed by a complex tectonic processes. Determining subbasin patterns and geological subsurface structure sometimes difficult to identified through geological qualitative analysis, especially in a minimum full rock outcrop condition. One of the geophysical methods that can be used to know the subbasin spreading and subsurface geological configuration is gravity method. The purpose of this research is examining the distribution pattern of sedimentary subbasin, structure patterns and subsurface geological configuration based on spectral analysis, two dimension, and three dimension gravity modeling. The result of spectral analysis shows that the average basement depth in North West Java basin is 3.3 Km. Based on the results of residual anomalies and 3D inversion shows that there are 5 subbasins; Bekasi Subbasin, Rengasdengklok Subbasin, Cikampek Subbasin, Subang Subbasin, and Majalengka Subbasin. The 2D modeling and the second vertical derivative (SVD) analysis result that the subbasin structure are controlled by some faults which forming horst-graben structures. Keywords : gravity, spectral analysis, second vertical derivative, gravity modelling, Northwest Java Basin